Evaluasi Aspek Teknis Kualitas Air Membran Ultrafiltrasi dalam Pengolahan Air Minum (Studi Kasus: IPA Krian Perumda Air Minum Sidoarjo) - Nada Fikna Salsabila; Eddy Setiadi Soedjono (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The Sidoarjo Regional Public Company (Perumda) is a regionally owned business entity that participates in managing and providing clean water which will be distributed to the people of Sidoarjo Regency. The Sidoarjo Drinking Water Company, especially the Krian IPA, uses the main channel to supply raw water from the Mangetan Canal which passes through seven sluice gates to irrigate 17,583 Ha of rice fields. The series of air treatment installations at Perumda Air Minum Sidoarjo are coagulation units, flocculation units, sedimentation units and ultrafiltration membranes. However, not all technology can be implemented optimally due to considerations of costs and Perumda personnel. The problem is that the ultrafiltration membrane unit at Perumda Air Minum Sidoarjo is not activated. Therefore, the aim of the research is to determine the ineffectiveness of ultrafiltration membranes at Perumda Air Minum Sidoarjo in terms of technical aspects, namely the quality of water resulting from membrane processing in 2016-2020. The results of the research on the technical aspect, namely data on water quality parameters for turbidity and color for 2016-2020, have complied with Minister of Health Regulation Number 2 of 2023 for drinking water quality standards, the rejection percentage for turbidity parameters was 69.39%. -95.48%; the percentage of color parameter rejection was 43.60% -61.6% with the resulting flux value decreasing.